Adaptation to reduced salinity affects the olfactory sensitivity of Senegalese sole (Solea senegalensis Kaup 1858) to Ca2+ and Na+ but not amino acids - Velez, Zélia (2014)
The Senegalese sole is a marine flatfish, which often penetrates into estuarine waters to feed. It cannot, however, survive in full freshwater. The current study investigated the effect of adaptation to low salinity (10‰) on olfactory responses to changes in environmental [Ca2+] and [Na+] and amino acids by the electro-encephalogram (EEG) recorded from the olfactory bulb. The sole showed olfactory responses to increases in environmental [Na+] and decreases in environmental [Ca2+]; sensitivity to Na+ was greater at 10‰ whereas sensitivity to Ca2+ was greater at 35‰. Decreased environmental [Na+] increased sensitivity to changes in [Ca2+] whereas increased environmental [Ca2+] decreased bulbar responses to changes in [Na+]. Sensitivity to amino acids was unaffected by external salinity. However, the absence of external Na+ strongly decreased bulbar responses to amino acids in fish adapted to 35‰ seawater but not in those at 10‰. The absence of external Ca2+ had no such effect at either salinity. This suggests that odorant-receptor binding and/or olfactory transduction is reliant on external Na+ (but not Ca2+) at higher salinities but the olfactory system is able to adapt to lower environmental [Na+]. Taken together, these results suggest that reductions of external salinity modulate olfactory sensitivity to environmental Ca2+ and Na+ but not amino acids. However, at low salinities, olfactory sensitivity to amino acids is maintained by decreasing reliance on external Na+.